2020
DOI: 10.3390/su12083352
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Jet Fuel Tax Changes on Air Transport, Employment, and the Environment in the US

Abstract: This paper presents an analysis of the effects of jet fuel taxes on air traffic, employment and emissions using a difference-in-difference design. These findings are relevant, as US airports identify how to respond to revenue shortfalls and support local employment in the recovery after Covid-19. Jet fuel tax cuts are considered pro-growth by airlines and stakeholders, however, limited research documents the impacts on airline operations, employment, and emissions, which is an increasing issue given growing so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“… Ref. : Aletta et al, 2020 , Basu et al, 2020 , Nižetić, 2020 , Sobieralski and Hubbard, 2020 ; Sub-theme 3. Energy systems and renewable fuels Keywords: Energy System Balancing; Electric Vehicles; Hybrid-Engine Vehicles; Fuel Consumption; Energy demand; Gasoline Passenger Cars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Ref. : Aletta et al, 2020 , Basu et al, 2020 , Nižetić, 2020 , Sobieralski and Hubbard, 2020 ; Sub-theme 3. Energy systems and renewable fuels Keywords: Energy System Balancing; Electric Vehicles; Hybrid-Engine Vehicles; Fuel Consumption; Energy demand; Gasoline Passenger Cars.…”
Section: Resultsmentioning
confidence: 99%
“…Air transport mobility and noise emissions. Several authors have attempted to estimate the reduction of CO footprint from aviation by using number of passengers, aircraft movements and indirect emissions released due to utilization of the different building facilities ( Baldasano, 2020 , Sobieralski and Hubbard, 2020 ). For instance, the estimations of Nižetić (2020) showed that carbon footprint emissions of European airports were reduced about a factor of 1.81–3.49, depending on the country.…”
Section: The Emerging Research Agenda In Human Mobility Behavior With...mentioning
confidence: 99%
“…Policy implications of these findings highlight the need to develop tools to curb these emissions. Private aviation user fees could serve this purpose as could tailored jet fuel taxes ( Gössling et al, 2017 , Sobieralski and Hubbard, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) Analyzing the relationship between pollutant emissions and lockdown policy The consideration of other influencing mechanism Hotspot: COVID-19 and energy policy Malliet et al. (2020) Introducing short-term economic and environment consequences of public policies Follow-up analysis to find out the long-term influence of the energy policies from a longer time scale Sobieralski and Hubbard (2020) Analyzing the general policy imposed to the whole nation Industry-level policy like jet fuel taxes on air traffic …”
Section: Resultsmentioning
confidence: 99%
“…Responding to COVID-19, governments have poured out fiscal expenditures and subsidies to combat surging infections and support residential livelihood, inducing a fiscal dilemma for many governments, especially in developing countries ( Khalid et al., 2020 ). Therefore, some countries turned to feasible energy policies to guarantee energy security and mitigate energy poverty during the pandemic ( Barbier, 2020 ; Sobieralski and Hubbard, 2020 ).…”
Section: Introductionmentioning
confidence: 99%